2014
DOI: 10.1161/strokeaha.114.006520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Living Alone on the Care and Outcomes of Patients With Acute Stroke

Abstract: Background and Purpose— Outcomes among patients living alone at stroke onset could be directly affected by reduced access to acute therapies or indirectly through the effects of social isolation. We examined the associations between living alone at home and acute stroke care and outcomes in the Registry of the Canadian Stroke Network. Methods— Between 2003 and 2008, 10 048 patients with acute stroke (87% ischemic, 13% hemorrhagic) who were living at hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 9 publications
3
64
3
Order By: Relevance
“…65 Living alone before stroke is associated with delays in arrival to hospital 66 and lower use of tissue-type plasminogen activator therapy, which likely affects PROMs. 67 Despite this, few of the studies reviewed here included social factors as potential confounders of sex differences with the exception of a small number of studies that adjusted for marital status or living alone. 18,42 A prospective study of ischemic stroke survivors found that social isolation, but not living alone, was associated with a 40% increase in the risk of cardiovascular events or death.…”
Section: Discussionmentioning
confidence: 99%
“…65 Living alone before stroke is associated with delays in arrival to hospital 66 and lower use of tissue-type plasminogen activator therapy, which likely affects PROMs. 67 Despite this, few of the studies reviewed here included social factors as potential confounders of sex differences with the exception of a small number of studies that adjusted for marital status or living alone. 18,42 A prospective study of ischemic stroke survivors found that social isolation, but not living alone, was associated with a 40% increase in the risk of cardiovascular events or death.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the personal social networks of fast (<6 h) and slow (>6 h) responders, building on prior literature which showed that being unmarried and living alone were risk factors for delay 49,50 . Our preliminary analysis revealed that patients who arrived later had close-knit networks, that is, smaller networks with higher constraint.…”
Section: Applications In Neurologymentioning
confidence: 99%
“…Stroke survivors living with their family or spouse arrive earlier at the hospital, receive more thrombolytic therapy, are more likely to return home [1], and receive more anticoagulants as secondary prevention [2], compared to stroke survivors living alone. Previous studies showed that stroke survivors’ living alone predicted mortality after stroke [3], which was especially true for male stroke survivors in the long-term perspective [4].…”
Section: Introductionmentioning
confidence: 99%